PRODUKSI BAHAN KERING DAN TINGGI TANAMAN RUMPUT SUDAN (Sorghum sudanense) PADA DEFOLIASI KE DUA TANPA PUPUK NITROGEN ULANGAN: THE DRY MATTER PRODUCTION AND HEIGH OF PLANT OF SUDAN GRASS (Sorghum sudanense) AT SECOND HARVEST UNDER DIFFERENT PLANT DISTANCES WITHOUT NITROGEN FERTILIZATION - Djoko Soetrisno; Onesimus Yoku (Fakultas Peternakan Universitas Papua, 2010)
The aim of this study were to obtain the dry matter (DM) production of sudan grass at second harvest under different plant distances without nitrogen fertilization and to decide whether fertilization have to be added or not. The design of the study was split plot design 4 x 7 with three blocks. The main plots were plant distances, namely :20x40 cm (J1), 40x40 cm(J2), 60x40 cm (J3) and 80x40 cm (J4), and each plot was divided into 7 subplots for randomly N application treaments, namely :N0 (P0); N75 (P1); N150 (P2); N225 (P3); N300 (P4); N375 (P5) dan N450 (P6). Phosphorus and K fertilizer were given at the same rate, that were 300 kg P2O5 and 150 kg K2O. Result of the study showed that planting distances, level of fertilizers and the interaction were significant (P<0.05) affected DM production and height of plants in the second harvest. The DM production in the second harvest was significantly lower (P<0.05) than the DM production in the first harvest. From this study it can be concluded that N fertilizer application should be given again after cutting in order to maintain the DM production of sudan grass in the next harvest.